Formation of the civil safety specialist’s personality on the basis of the value of health: humanistic paradigm - Klos, L.; Mukan, N.; Kryshtanovych, M. (Problems of Engineer-Pedagogical Education, 2020)
The article deals with the question of vocational training of future civil safety professionals based on the humanistic paradigm of modern education. Particular emphasis is placed on the importance of the formation of the occupational health of civil safety specialists as a tool of their professional suitability, professional formation and development, a means of preventing occupational deformities and professional burnout. The importance of health for a single individual and modern society as a whole is characterized as well as the dependence of “the value of health” on individual health experiences is illustrated. The article highlights the need to implement health behaviour and health-related activities for a successful individual health experience. The modern views on the attitude to health within the system of “an individual-health-society” are analysed. The types of attitude to health are presented from the perspective of the individual (subject-object, intersubjective, subjective) and from the positions of the mass consciousness (active positive, indifferent and active negative). A healthy personality is characterised based on conceptual fundamentals of humanistic psychology. It is determined that the provision of successful vocational training of highly qualified and competent civil safety specialists is facilitated by the humanization of the educational process and the humanization of the content of the training itself. The role of health value, health preservation as a worldview orientation of future civil safety professionals, contributing to the development of occupational health and the overall healthy personality of the specialist are substantiated. Further research on this issue involves examining the results of the practical implementation of the ideas of the humanistic paradigm in education and the humanization of the content of education of future professionals in the field of civil safety by means of healthcare and value attitude to health.